Passively Q-switched ytterbium-doped fiber laser employing samarium oxide as saturable absorber - Rusdi, Khairul Nizam; Jefri, Afiq Arif Aminuddin; Zulkifli, Nur Farhanah; Mohamad Samsamnun, Farina Saffa; Mahyuddin, Mohamad Badrol Hisyam; Harun, Sulaiman Wadi; Zainal Abidin, Mohd. Shahnan; Saidin, Norazlina (IIUM Press, International Islamic University Malaysia, 2021)
The rapid developments in transition metal dichalcogenide materials as saturable absorbers (SAs) have been reported to be efficient materials for generating Q-switched fiber lasers. In this paper, we report on the use of samarium oxide (Sm2O3)saturable absorber (SA) for 1-micron Q-switched fiber laser generation. The Sm2O3 thinfilm SA was constructed in-house through which the Sm2O3 powder was mixed and stirredin polyvinyl alcohol (PVA) solution. It was then integrated into the ytterbium-doped fiberlaser (YDFL) ring cavity, hence producing a sequence of Q-switched pulsed lasers at1062.49 nm wavelength. The stable pulse train appeared from 69.97 to 111.1 kHz betweenthe applied pump power of 57 mW to 96 mW. The signal-to-noise ratio (SNR) of 38.56dB was recorded at the 57 mW pump power, whereas the pulse energy raised until 15.21nJ at 96 mW. These results showed that the Sm2O3 could be a favourable SA material toiniatiate Q-switched ytterbium-doped pulsed fiber laser. ********************************************************************************* Perkembangan pesat dalam bahan logam peralihan dichalcogenide sebagai bahan penyerap boleh larut (SAs) telah dilaporkan sebagai kaedah yang berkesan bagi menjana laser fiber Q-switched. Kajian ini menggunakan samarium oksida (Sm2O3) saturable absorber (SA) bagi menjana laser gentian Q-switched 1-Micron. Filem nipis Sm2O3 SA telah dihasilkan melalui campuran serbuk Sm2O3 ke dalam cecair polivinil alkohol (PVA) dalam persekitaran makmal. Kemudian, ia diintegrasi ke dalam rongga gelang laser gentian dop-ytterbium (YDFL), lalu menghasilkan denyut laser Q-switched stabil pada jarak gelombang 1062.49 nm. Denyutan stabil muncul dari 69.97 kepada 111.1 kHz pada kuasa pam yang dikenakan antara 57 mW hingga 96 mW. Nisbah isyarat-hinggar (SNR) pada 38.56 dB telah direkodkan pada pam kuasa 57 mW, sementara denyut tenaga ditingkatkan kepada 15.21 nJ pada 96 mW. Keputusan menunjukkan Sm2O3 merupakan bahan SA penggalak yang memuaskan bagi menjana denyut laser gentian dop-ytterbium Q-switched.